Pengaruh Bimbingan Doa Terhadap Kualitas Tidur Pasien Congestive Heart Failure yang Mengalami Dispnea - Kasron Kasron; Susilawati Susilawati; Wishnu Subroto (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Introduction : Congestive Heart Failure (CHF) is a terminal disease that causes various kinds of clinical manifestations that are very disturbing to the sufferer, such as dyspnea, and dyspnea in CHF patients can cause a sleep disorder known as Sleep-disordered breathing (SDB). The aim of this study was to determine the effect of providing prayer guidance on the sleep quality of CHF patients with dyspnea. Methods : Pre-post test research approach with control group designe. The sampling method used accidental sampling for 5 months, the number of respondents in the intervention group was 10 and the control group was also 10 respondents, the analysis used Wilcoxon and Mann Whitney. Results : The results showed that 30% of respondents' sleep quality was in the very poor category, and showed no significant difference between sleep quality before and after prayer guidance (p-value: 0.350). Conclusion : the study was that there was no effect of providing prayer guidance on the sleep quality of CHF patients with dyspnea. Suggestions for this research is to continue the research by increasing the number of respondents.